The repulsive effects of the tax burden on the generation of wealth in Brazil - Lima, Lauro Vinício de Almeida; Machado, Márcia Reis (Revista de Administração da UFSM, 2020)
Purpose – This research was aimed at verifying the influence of the tax burden on the value added produced by publicly traded companies listed in Brazil Bolsa Balcão (B3). Design/methodology/approach – The study had a quantitative approach and the sample period was from 2010 to 2016. Given the complexity of the Brazilian tax burden – characterized by high tax rates and confusing legislation – and the importance of value added as an accounting metric with economic impact, this research relied on the public choice theory and the elasticity of taxable income to analyze the relationship between the level of tax burden and the process of wealth generation in Brazilian companies. Findings – The empirical evidence found in this study corroborates the theoretical understanding that the tax burden in Brazil exerts a negative influence on the value added produced by companies. Practical and Social implications – This conclusion is a relevant assessment for society as a whole, as it is necessary to protect and maximize companies’ wealth-adding process, since it is the resources produced by companies that will be shared in the economy with society, whose development depends on the wealth creation process. Originality – The use of the added value produced as a metric of efficiency or saturation of the tax burden borne by companies in the Brazilian market.